Evaluating person-centered care in neurological outpatient care: a mixed-methods content validity study - Mia Olsson; Sidona-Valentina Bala; Peter Hagell (BMC Nursing, 2024)
Abstract Background Person-centered care (PCC) is gaining increased attention. PCC concerns the whole person behind the disease and can improve care for people with long-term conditions such as multiple sclerosis (MS) and Parkinson’s disease (PD). However, there is a lack of tools to assess PCC from the patients’ perspective, particularly in outpatient care. The Person-Centered Care instrument for outpatient care (PCCoc) is an instrument under development with the intention to fill this gap. The aim of this study was to test the user-friendliness and content validity of the PCCoc as experienced by persons with MS and PD in neurological outpatient care. Methods Twenty persons with MS or PD completed the 35-item PCCoc followed by an interview regarding the instrument’s intelligibility and ease of use to assess its user-friendliness. Participants then rated the relevance of each item. These ratings were used to calculate the content validity index (CVI) for individual items (I-CVI) and for the overall scale (S-CVI). Results It took a median of 5 min for participants to complete the PCCoc. Instrument instructions were found clear, items easy to understand, and response categories distinct. No important missing areas were reported. I-CVI values ranged between 0.75 and 1, and S-CVI was 0.96. Conclusions We found support for the user-friendliness and content validity of the PCCoc among persons with MS and PD, suggesting that the PCCoc can be useful for evaluating and developing PCC in neurological outpatient care. Further testing in broader contexts, including psychometric testing, is warranted to establish its usefulness.